Porous hydroxyapatite scaffolds by polymer sponge method - Fook, A. C. B. M.; Aparecida, A. H. [UNESP]; Fideles, T. B.; Costa, R. C.; Fook, M. V. L.; Prado, M.; Zavaglia, C. (Trans Tech Publications Ltd, 2009)
This study aimed to develop porous hydroxyapatite scaffold for bone regeneration using the replica of the polymeric sponge technique. Polyurethane sponges were used with varying densities to obtain the scaffolds. The results indicate the porous HA scaffolds developed in this study as potential materials for application as bone substitutes to have high porosity (> 70%), chemical composition, interconnectivity and pore sizes appropriate to the bone regeneration.
Keywords: Tissue engineering; scaffold; hydroxyapatite; bone regeneration